Dança, vida, vontade, mudança: a dança e a apresentação da apatia em pacientes com a doença de Parkinson - FURTADO, Viviane Kharine Teixeira (2021)
Parkinson's disease (PD) is a chronic neurodegenerative disease which presents a range of symptoms that can be classified as motor and non-motor. Apathy is a neuropsychiatric disorder that has main characteristic loss of motivation, with high prevalence among patients with PD. Dance is one of the practices that has been gaining growing space in Brazil as a preventive strategy of sedentarism, to delay senility and promote quality of life among the elderly. The present study was developed to investigate the potential of dance in reducing the presentation of apathy in patients with PD. Patients with PD diagnosis and under pharmacological scheme participated regularly in weekly dance classes, two classes per week with duration of 1 hour per session, under a protocol developed specifically for the work of the specific needs of the patient with Parkinson's. We used the Apathy Scale protocol to evaluate patients when they joined the program, followed by retest after six months of intervention. Qualitative analyses of the patients' own testimonials, as well as the caregivers and volunteer students of the project revealed a subjective perception of improvement in the motivational, quality of life and motor aspects of these patients. Quantitative analyses of the scores obtained in the apathy test revealed a significant difference in the averages of the group between the analyses performed before (19.77 ± 2.88) and after (12.44 ± 1.82) the six-month period of dance classes. The reduction in the apathy score between the periods was 37.52%. Due to its pleasant features and stimulation of several neural systems, dance can contribute significantly to the improvement of well-being and to the reduction of the rate of symptomatic progression of PD patients.